Fading Voices: A 10-Year Trend Within an Agricultural Advertiser-Media-Reader Triad - Stephen A. Banning; James F. Evans (Journal of Applied Communications, 2001)
Research reported here addresses effective communications within agriculture by examining power relationships within the agricultural publishing triad: advertisers, periodicals and producer readers. A 10-year analysis using mail surveys among agricultural print journalists explores recent changes within this triad, including perceptions of trends in the levels, kinds, and effects of advertiser influence on editorial content of U.S. commercial farm periodicals. Results reveal increasing advertiser-related pressure on the journalists. Other findings examine perceived harm to the profession, publication policies used, and differences in response related to gender and age. Authors discuss implications and offer steps for follow-up through research and professional education.